Prototype automated input tool for Android fuzzing - Ang, Brenda Ting Le (2019)
The objective of this project is to create a tool that aids in the process of Android applications testing but automating the inputting of user details process. After development and testing, evaluations were done, and recommendations and conclusions were drawn to assess the performance of the tool. Android applications have been in the spotlight especially in the recent years. To make sure that they are suitable for release, tests have to be done to ensure that the applications do no have flaws. Although many tools and techniques have been developed to aid in this process, testing of Android applications is still not an easy task. This project has created a tool to aid in the testing process while automating the process of filling in inputs. Mechanisms implemented, and inner workings were detailed, and an evaluation was drawn on the performance of the tool created. The evaluation was done on how well the tool was able to sign-up for four different Android applications with little help from the person executing the tool. Different input types, and requirements of the different Android applications impacted the performance of the tool, however, within the scope of this project, the tool can be considered to have achieved its purposes.